Constrângeri și provocări în dezvoltarea aptitudinilor digitale pentru forța de muncă din România - Artene, Lucian (Calitatea Vieții, 2023)
In a context marked by the continuous increase for digitization, the evolution of digital skills among employees becomes an essential aspect for competitiveness and economic adaptability. This study focuses on the Romanian workforce, highlighting a lower level of digital skills compared to the European average. The main purpose of the research is to analyze the specific barriers that prevent the development of digital skills for Romanian workers. The research has two main objectives: identifying the causes of the low level of digital skills among Romanian employees, respectively analyzing the degree to which the identified causes contribute to the low level of digital skills in Romania. This article addresses the concept of "digital aptitude" and explores the current trends regarding the digital skills of the workforce in Romania. A detailed analysis of the causes of the low level of digital skills is carried out by synthesizing/ reviewing international specialized literature. The methodology includes the synthesis of specialized literature on the subject of constraining the development of digital skills, together with the analysis of statistical data and official documents to identify relevant trends. The results of this research highlight the role of material, temporal, educational, motivational and sociocultural factors in explaining the low level of digital skills. In Romania, material barriers materialize in a tendency of companies to invest little in digital technologies for employees; the temporal ones reflect the longer working time, compared to the EU average; the educational ones include the low participation of Romanian employees in education and training activities; the psychological ones emphasize the low motivation of long-term employees, lower than that of job changers; the sociocultural ones refer to certain sociodemographic characteristics, such as older age and rurality, which are correlated with a lower level of digital skills. The relevance of this research is both theoretical, contributing to knowledge in an essential field in the contemporary period, and a practical dimension, thanks to the recommendations made based on the identified barriers. The focus is on the need for a comprehensive approach to the development of digital skills for the workforce, in the context of the development and implementation of public policies, but also policies at the company level. In the absence of addressing all the identified factors, initiatives aimed at developing digital skills may not achieve the proposed objectives, and may not be adapted to the real needs of the target population.